Nazira PRODUCTIVE ACTIVITIES FOR DEVELOPING STRATEGIC COMPETENCE IN FOREIGN LANGUAGE ACQUISITION: PRODUCTIVE ACTIVITIES FOR DEVELOPING STRATEGIC COMPETENCE IN FOREIGN LANGUAGE ACQUISITION - Abraimova, Nazira (Журнал иностранных языков и лингвистики, 2022)
As Canale declared, strategic competence is one of the most important components of communicative competence, which deals with improving learners’ verbal and non-verbal communication. Thus its strategic trainings are completely teachable for classroom. In order to reach fluent speech among foreign language learners, teachers should utilize effective strategic activities during the classroom trainings. As we are future foreign language specialists, I would like to investigate various types of productive activities for developing students’ strategic competence. Besides that I would like to give complete information about the procedures of those classroom activities.